PENGARUH MINUM TABLET FE TERHADAP ANEMIA PADA REMAJA PUTRI DI DESA PACOR KECAMATAN KUTOARJO KABUPATEN PURWOREJO - Ika Zuliyanti, Nurma; Denata Maisyina, Cut; Ayu Pangesti, Diah (Jurnal Komunikasi Kesehatan, 2025)
The high incidence of anemia in adolescent girls is due to the fact that there are still many adolescent girlswho are not used to consuming Fe tablets. The results of a preliminary survey among young women in PacorVillage show that compliance with taking Fe tablets is still low, so they need to be given vitamins, namely Fetablets, to prevent anemia. To determine the effect of taking Fe tablets on anemia in young women in PacorVillage, Kutoarjo District, Purworejo Regency. This research used a pre-experimental design with a OneGroup Pretest - Posttest design. The population in this study was 184 young women. Determining the numberof samples using the Slovin formula obtained a sample of 36. The sampling technique used purposive samplingtechnique. The research time was from 26 May to 9 June 2025. Data analysis used the Normality Test, then theKolmogorov-Smirnov and Shapiro-Wilk tests, and the Paired t-Test. The results of data analysis obtained a tvalue of -7.246 and a probability of 0.000 (smaller than alpha 0.05). There is an effect of taking Fe tablets onthe incidence of anemia in Pacor Village, Kutoarjo District, Purworejo Regency. It is hoped that young womenwill be disciplined in taking Fe tablets according to the recommended amount and can increase teenagers'knowledge about anemia.